Potential Protective Activities of Extracts of Phellinus linteus and the Altered Expressions of GSTM3 on Age-Related Cataract. (21st January 2021) - Lin, Cheng-Hsiu; Shih, Chun-Ching
Abstract : Age-related cataract (ARC) is one of the leading causes of visual impairment and blindness worldwide among the elderly. Here, we used sodium selenite-induced cataract mouse model, which shares with similarities with human senile cataract to investigate whether the extracts of Phellinus linteus (PLE) could have the potential protective effects of ARC or not. The mice pups were randomly divided into 4 treatment groups ( n = 7): (1) normal saline on postpartum day 26; (2) Na selenite injected s.c on day 26; (3) Na selenite s.c on day 26+ gavaged PLE (40 mg/kg) on days 26–47; and (4) Na selenite s.c on day 26 + resveratrol on days 26–47. On day 47, encapsulated lenses and plasma were analyzed for the levels of glutathione (GSH), superoxide dismutase (SOD), and malondialdehyde (MDA), a marker of lipid peroxidation. Lens epithelial cells (LECs) were also analyzed for the mRNA and protein expressions of glutathione S-transferase Mu ( GSTM3 ). We demonstrated that PLE could prevent selenite-induced oxidative stress and cataract formation in mice by higher GSH and SOD and lower MDA in LECs, plasma, and liver tissues and the increases in the mRNA and protein expressions of GSTM3 in LECs. Our data show the increasing oxidative stress in selenite-induced cataract mice. Our data reveal the benefits of PLE for preventive activity in selenite-induced cataract in mice and there is a good possibility that PLE could ameliorate human senile cataract.